Evaluating hs-cTnI serum levels and cTnI gene expression compared with cardiac nuclear scan in patients with angina pectoris: Validity of cTnI serum and gene expression in angina pectoris - Zhang, Guifang; Zhan, Jiang; Lei, Hong; Zhu, HaiYan; He, xiaowei (Cellular and Molecular Biology, 2023)
Exercise stress can cause reversible myocardial ischemia in people with coronary artery disease (CAD). On the other hand, the new troponin biomarker with high sensitivity can detect faster and small amounts of troponin in blood circulation. The present study aimed to investigate the serum troponin level following exercise stress and the result of nuclear heart scans as the gold standard. For this purpose, 93 patients with stable angina and no history of known CAD and organic disease were included in this cross-sectional study. The serum level of the highly sensitive cardiac troponin I (hs-cTnI) was measured 75 minutes after the peak of the exercise test and reached at least 85% of the maximum heart rate. It was compared with the rate of reversible myocardial ischemia based on the nuclear heart scan, the three-month prognosis and the persistence of chest pain were investigated. Also, the expression level of the cTnI gene was evaluated by real-time PCR technique. The results showed that the average age of the patients was 58.9+12.4 years, and 62 (66.66%) patients were female. Reversible myocardial ischemia was observed in 31 patients. The relationship between hs-cTI level and the rate of reversible ischemia cases was significant (p = 0.0041). Also, the cTnI gene expression showed the same results as the serum level. According to the heart nuclear scan report, the hs-cTnI value above 1.6ng/dl had a specificity of 72% and sensitivity of 66%, a positive predictive value of 53%, and a negative predictive value of 78%. There was no significant relationship between hs-cTnI level and prognosis and the continuation of chest pain in patients after three months. Generally, the serum level of high-sensitivity cardiac troponin was higher after exercise in the group with reversible myocardial ischemia.